﻿Anticancer potential of garlic bioactive constituents: Allicin, Z-ajoene, and organosulfur compounds - Wamidh H. Talib; Sally Atawneh; Areen Nabil Shakhatreh; Ghyda’a Nabil Shakhatreh; Islam Subhi Rasheed aljarrah; Reem Ali Hamed; Doaa Adel banyyounes; Intisar Hadi Al-Yasari (Pharmacia, 2024)
Cancer, a formidable disease with a significant mortality rate, continues to claim the lives of thousands of individuals annually in contemporary society. Conventional cancer therapies are notorious for their substantial adverse effects and lack of specificity. Within the context of neoplastic development, cancer hallmarks represent fundamental biological properties that cancer cells progressively acquire. A promising approach for combating cancer involves the simultaneous targeting of multiple cancer hallmarks. Plant-derived natural compounds stand out as a promising reservoir for the development of novel and more efficacious anticancer therapeutics due to their structural diversity and minimal toxicity profiles. Garlic (Allium sativum) has garnered considerable attention for its established anti-cancer properties over the years. Within garlic, a myriad of bioactive constituents, including organosulfur compounds, flavonoids, and phenolic compounds, exhibit distinct effects on cancer cells. The objective of this review paper is to furnish a comprehensive elucidation of the mechanisms underpinning the anticancer actions of garlic. The elucidated findings from the studies encompassed within this review not only contribute to a more profound comprehension of the anti-cancer properties of garlic but also serve as a robust foundation upon which researchers and healthcare practitioners can formulate enhanced anticancer pharmaceuticals grounded in natural garlic compounds.